Discovery of Novel Anti-cryptosporidial Activities From Natural Products by in vitro High-Throughput Phenotypic Screening - Jin, Zi; Ma, Jingbo; Zhu, Guan; Zhang, Haili (Frontiers in Microbiology, 2019)
Cryptosporidium parvum is a globally distributed zoonotic protozoan parasite of both medical and veterinary importance. Nitazoxanide is the only FDA-approved drug to treat cryptosporidiosis in immunocompetent people, but it is not fully effective. There is no drug approved by FDA for use in immunocompromised patients or in animals. In the present study, we conducted phenotypic screening of 800 nature products with defined chemical structures for potential novel activity against the growth of C. parvum in vitro. We identified a large number of compounds showing low to sub-micromolar anti-cryptosporidial activity, and fully characterized 16 top hits for anti-parasitic efficacies in vitro (EC50 values from 0.122 to 3.940 μM), cytotoxicity (TC50 values from 6.31 to >100 μM) and their safety margins. Among them, 11 compounds were derived from plants with EC50 values from 0.267 to 3.940 μM (i.e., cedrelone, deoxysappanone B 7,4'-dimethyl ether (Deox B 7,4), tanshinone IIA, baicalein, deoxysappanone B 7,3'-dimethyl ether acetate, daunorubicin, dihydrogambogic acid, deacetylgedunin, deacetoxy-7-oxogedunin, dihydrotanshinone I, 2,3,4'-trihydroxy-4-methoxybenzophenone, and 3-deoxo-3beta-hydroxy-mexicanolide 16-enol ether). Three compounds with sub-micromolar EC50 values (i.e., cedrelone, Deox B 7,4 and baicalein) were further investigated for their effectiveness on various parasite developmental stages in vitro. Cedrelone and baicalein were more effective than Dexo B 7,4 when treating parasite for shorter periods of time, but all three compounds could kill the parasite irreversibly. These findings provide us a large selection of new structures derived from natural products to be explored for developing anti-cryptosporidial therapeutics.